PENATAAN KAWASAN TEPIAN SUNGAI SEBAGAI RUANG TERBUKA DI MURUNG KENANGA, MARTAPURA - Sulistyaningsih, Dwi; Mentayani, Ira (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Riverbanks in Murung Kenanga have the potential to be developed as green open space on the banks of a river that can maintain sustainability the function of the river and becomes a forum for community outreach. This potential has not been fully developed. The existing condition of the river bank which is used as shelter and disposal, causing edge damage river. The conditions of slums around the area become an obstacle to additional handling of this area. Therefore, this area requires the arrangement is right on target and has a positive impact on the surrounding environment. The urban acupuncture method was chosen by making the riverbank area in Murung Kenanga as an open green space and a positive activity point for the surrounding community. The principle of the application of urban acupuncture used in design points in the region is the target focus, low cost applies in every situation, instant effects, facilitate needs, and simple actions. The method supports the concept of environmental & recreation waterfront that is applied by making the area river banks as open spaces that are creative and considerate of the environment. Application of concepts and methods applied through, 1) Quality improvement regional environment through exploiting the natural potential and returning functions rivers with the development of pond areas, the use of riverbank vegetation and ecological plaster 2) Utilization of river banks as recreation areas with designing playgrounds & reading for children, relaxing parks, sports parks, and areas culinary 3) Triggering positive community activities by providing open space green equipped with supporting facilities therein.